Global, regional, and national burdens of pertussis among adults: a systematic analysis of age-specific trends using Global Burden of Diseases 2021 data - Kangguo Li; Jiadong Wu; Ruixin Zhang; Yulun Xie; Zecheng Zhou; Qi Yin; Qi Chen; Jia Rui; Xuhua Guan; Zeyu Zhao; Tianmu Chen (Infectious Diseases of Poverty)
Abstract Background Despite the high coverage of childhood vaccination, pertussis remains a significant global health challenge, with increasing adult cases attributed to waning immunity and enhanced diagnostic capability. This study quantified the global burden of pertussis in adults from 1990 to 2021 and evaluated the impact of the COVID-19 pandemic on disease trends. Methods Using data from the Global Burden of Disease Study 2021, we assessed pertussis incidence and disability-adjusted life years (DALYs) in adults, stratified by age, sex, sociodemographic factors, and geographic regions. Temporal trends were analysed using joinpoint regression to detect significant changes and calculate the average annual percentage change (AAPC). An exponential smoothing state-space model with hierarchical forecast reconciliation was used to estimate the impact of the COVID-19 pandemic on pertussis burden. Results Globally, the incidence rate of adult pertussis declined from 17.44 per 100,000 population in 1990 to 9.00 per 100,000 in 2019, and fell sharply to 2.70 per 100,000 by 2021. DALYs rates followed a similar trend. The burden was consistently highest in low Socio-demographic Index (SDI) countries, where the 2019 incidence rate was over four times that of high SDI countries (18.59 vs. 3.96 per 100,000). Between 1990 and 2019, incidence numbers increased in low SDI countries [AAPC: 0.63%; 95% confidence interval: 0.36%, 0.91%] and in older adults (AAPC > 0), despite falling incidence rates. From 2009 to 2019, incidence rates increased in 84 countries. During the COVID-19 pandemic, estimates based on the model indicated a 58.41% reduction in incidence and a 50.34% decrease in DALYs. Conclusions Although the global incidence of adult pertussis has declined over the past three decades, a resurgence from 2009 to 2019, particularly in low-income regions and specific age groups, underscores the persistent challenges. The sharp decline during the COVID-19 pandemic highlights the importance of public health and social measures. These findings emphasise the need for targeted vaccination strategies and sustained surveillance to address regional disparities and prevent the resurgence of the disease. Graphical Abstract